Beginning Google Maps API 3 - Svennerberg, Gabriel. (Apress, 2010)
This book is about the next generation of the Google Maps API. It will provide the reader with the skills and knowledge necessary to incorporate Google Maps version 3 on web pages in both desktop and mobile browsers. It also describes how to deal with common problems that most map developers encounter at some point, like performance and usability issues with having too many markers and possible solutions to that. Introduction to the Google Maps API version 3 Solutions to common problems most developers encounters (too many markers, common JavaScript pitfalls) Best practices using HTML/CSS/JavaScript and Google Maps